TOPICAL ISSUES OF TRAINING OF GMP INSPECTORS - V. N. Shestakov; Yu. V. Podpruzhnikov (Разработка и регистрация лекарственных средств, 2019)
The main requirements for a quality system of GMP-inspectorate in terms of inspectors’ appropriate training were described and analyzed. The existing international recommendations in this area were summarized. It was shown that the training of inspectors should be organized and carried out on such principles as systemacy, consistency, professionalism and performance of the international recommendations on training. The additional professional retraining program for GMP inspectors/auditors was developed, tested, and approved. The developed program can be used successfully for training of GMP-inspectors from regulatory authorities of the states that are members of Eurasian Economic Union. The program can be used successfully for training of GMP-inspectors from regulatory authorities of the states that are members of BRICS after some adaptation also.